2009
DOI: 10.1002/jemt.20640
|View full text |Cite
|
Sign up to set email alerts
|

Toxic effect of environmental acid‐stress on the sperm of a hill‐stream fish Devario aequipinnatus: A scanning electron microscopic evaluation

Abstract: Environmental stress due to acidic pH of water was found to be one of the major factors leading to toxic effects on the sperm of a hill-stream fish Devario aequipinnatus of Meghalaya, India. The Scanning Electron Microscopy of the transverse section of testes of the fish collected from its natural habitat with acidic pH (5.6-6.0) showed that the sperms were clumped together and their tails were either absent or were of extremely small length. The acrosome and midpiece were also not well differentiated. When th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 11 publications
0
18
0
Order By: Relevance
“…Scanning electron microscopy, due to its large depth of field and high resolving power appears to be important in studying surface ultra structural morphology and organization of the spermatozoa. Many authors could use this versatile tool with success in understanding the ultra structural morphology of sperm and other structures either in normal fish or in fish experiencing some kinds of stress (Dey et al,2009a,b; Psenicka et al,2007). The detail understanding on the cellular features of spermatozoa was possible through extensive studies involving TEM (Gusmao‐Pompiani et al,2009; Gwo et al,1995; Matos et al,1999; Pecio,2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Scanning electron microscopy, due to its large depth of field and high resolving power appears to be important in studying surface ultra structural morphology and organization of the spermatozoa. Many authors could use this versatile tool with success in understanding the ultra structural morphology of sperm and other structures either in normal fish or in fish experiencing some kinds of stress (Dey et al,2009a,b; Psenicka et al,2007). The detail understanding on the cellular features of spermatozoa was possible through extensive studies involving TEM (Gusmao‐Pompiani et al,2009; Gwo et al,1995; Matos et al,1999; Pecio,2003).…”
Section: Introductionmentioning
confidence: 99%
“…Matos et al (2002) studied biflagellate spermatozoon structure of the hermaphrodite fish Satanoperca juripari . It is to be noted in this context that despite a large number of published works in the existing literature about sperm ultra structure, very few reports exist on the same topic with reference to environmental stress and pollution (Dey et al,2009a; Psenicka et al,2008). …”
Section: Introductionmentioning
confidence: 99%
“…Blanckenhorn and Hellriegel, 2002); most other stressors have, in contrast, been shown to lead to decreased sperm length (e.g. Dey et al, 2009;Immler et al, 2010). These changes subsequently can have a significant impact on male reproductive success (Billard, 1978;Stoss, 1983;Gage et al, 2004;Alavi and Cosson, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…It is thus concluded that there are ample opportunities in using SEM of fish scale micro structures in determining species specificity in fish for taxonomical applications and other important applications (Dey et al, 1994(Dey et al, , 2008Psenicka et al, 2008;Ravneet et al, 2009). The aforementioned structures can be resolved precisely with the help of SEM.…”
Section: Resultsmentioning
confidence: 99%